The female baristas' motivation in Watampone - Hasni, Hasni; Islami, Nur Ainul (Pusat Studi Gender dan Anak, 2024)
The number of coffee roasters in the form of cafes in South Sulawesi continues to increase. Similarly, the number of baristas who are at the forefront of these activities has also increased, although the number of female baristas is still lower than that of male baristas. With that background, this study aims to understand the work motivation of female baristas from the perspective of the Need Hierarchical Theory and the Two Factor Theory. The qualitative research method was conducted through semi-structured interviews with five female baristas. The research was conducted in Watampone, Bone Regency, South Sulawesi. The research results showed that, in general, female baristas felt happy with their jobs because they provided a sufficient income. Therefore, from the perspective of the Need Hierarchical Theory, they had at least reached the third level, which is social needs. Meanwhile, based on the Two Factor Theory, in general, female baristas have been able to accept the conditions provided by their workplace, although not all have reached the desired level of satisfaction, so they continue their profession as baristas.